Caregiver burden and stress in psychiatric hospital admission - Pedroso,Tássia Ghissoni (2019)
ABSTRACT Objective: to evaluate the relation between sociodemographics factors, stress and burden of care of family caregivers of patients at a psychiatric hospital admission. Method: quantitative study, with a cross-sectional correlation design. A total of 112 family caregivers participated, older than 18, in a Brazilian psychiatric hospital. A sociodemographic questionnaire was used to collect data, the Zarit Burden Interview and LIPP Adult Stress Symptom Inventory. Results: burden of care in family caregivers at a psychiatric hospital admission was significantly associated with stress (p=0.000). The psychological symptoms of stress predicted severe burden. Most caregivers presented a moderate or severe burden, with 52.7% in the resistance phase of stress; 66.1% presented psychological symptoms. Conclusion: results show the alarming situation of caregivers of patients from a psychiatric hospital, evidencing their own vulnerability to illness. Indeed, the during admission in a psychiatric hospital, not only patients need care, but also their caregivers.